2018
DOI: 10.4103/ijmr.ijmr_403_17
|View full text |Cite
|
Sign up to set email alerts
|

S961, a biosynthetic insulin receptor antagonist, downregulates insulin receptor expression & suppresses the growth of breast cancer cells

Abstract: Background & objectives:Insulin resistance associated with hyperinsulinaemia and overexpression of insulin receptors (IRs) have been intricately linked to the pathogenesis and treatment outcomes of the breast carcinoma. Studies have revealed that upregulated expression of IRs in breast cancer pathogenesis regulates several aspects of the malignant phenotype, including cell proliferation and metastasis. This study was aimed to investigate the pivotal role of an IR antagonist S961 on IR signalling and other biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Activation of IR phosphorylates IR substrate (IRS) which, in turn, activates multiple downstream signal transduction effectors such as phosphoinositide 3-kinase (PI3K)/AKT and ERK pathways [38,39]. As a result, IR regulates several fundamental cellular processes such as cell proliferation, differentiation, cell cycle, and migration [17]. Insulin-like growth factor 1 receptor (IGF-1R) is a common dimerization partner of IR [5,7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Activation of IR phosphorylates IR substrate (IRS) which, in turn, activates multiple downstream signal transduction effectors such as phosphoinositide 3-kinase (PI3K)/AKT and ERK pathways [38,39]. As a result, IR regulates several fundamental cellular processes such as cell proliferation, differentiation, cell cycle, and migration [17]. Insulin-like growth factor 1 receptor (IGF-1R) is a common dimerization partner of IR [5,7].…”
Section: Discussionmentioning
confidence: 99%
“…IR had received less attention as a therapeutic target in cancer because of the potential impact on glucose homeostasis [7]. Nevertheless, recent evidence from in vitro and in vivo studies had indicated that inhibitors of IR have potent antitumor activity [17,[57][58][59][60]. Sharma et al showed that IR antagonist S961 suppressed growth and downregulated IR expression in breast cancer cells [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations